5(x+6)=3(x-5)

Simple and best practice solution for 5(x+6)=3(x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+6)=3(x-5) equation:


Simplifying
5(x + 6) = 3(x + -5)

Reorder the terms:
5(6 + x) = 3(x + -5)
(6 * 5 + x * 5) = 3(x + -5)
(30 + 5x) = 3(x + -5)

Reorder the terms:
30 + 5x = 3(-5 + x)
30 + 5x = (-5 * 3 + x * 3)
30 + 5x = (-15 + 3x)

Solving
30 + 5x = -15 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
30 + 5x + -3x = -15 + 3x + -3x

Combine like terms: 5x + -3x = 2x
30 + 2x = -15 + 3x + -3x

Combine like terms: 3x + -3x = 0
30 + 2x = -15 + 0
30 + 2x = -15

Add '-30' to each side of the equation.
30 + -30 + 2x = -15 + -30

Combine like terms: 30 + -30 = 0
0 + 2x = -15 + -30
2x = -15 + -30

Combine like terms: -15 + -30 = -45
2x = -45

Divide each side by '2'.
x = -22.5

Simplifying
x = -22.5

See similar equations:

| 3y+6=-18 | | -0.375h=-12 | | 36x+159= | | 5x-15=30+2 | | 2x+1y=78 | | -2.6h=-12 | | 8(x+4)=6(x-2) | | (5x+4)(3x+2)=(7x-1)(3x-5)+60x-51 | | 2(5+w)=94-w | | 1=7-3x | | 7p=7(4p+9) | | (5+2w)+w=94 | | x=(-8) | | 5m-2m+4m-6m= | | 4.7x-39=2.3x+9 | | 6(6x+6)=36x+36 | | 6ab-3ba= | | 5x^2-36x-108=0 | | 14k-70=42 | | 4x^2-10x-288=x^2-22x | | 2(x)+x=180-63 | | 2k-10=-42 | | x+(3x-10)=90 | | (7*3)-n=9 | | 9/5•42 | | Logb(6x^4)-7logb(x)=0 | | 8a^2-98=0 | | 4÷102/3 | | 4/3(-12=160 | | -5(7-6b)=-6b-35 | | 3=19.5 | | jk=6 |

Equations solver categories